2011
DOI: 10.2214/ajr.10.5109
|View full text |Cite
|
Sign up to set email alerts
|

Swine-Origin Influenza A (H1N1) Viral Infection: Thoracic Findings on CT

Abstract: The imaging findings seen in patients with H1N1 infection include consolidations, ground-glass opacities, interlobular septal thickening, small nodules, and findings suggestive of small airways disease, among others. Definitive diagnosis is based on correlation of the CT findings with the clinical symptoms and laboratory test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 15 publications
6
25
0
Order By: Relevance
“…One patient in our study showed the crazy-paving pattern. This finding was previously described in immunocompetent patients (21,22). Another patient showed signs of chronic disease with irregular linear opacities and bronchiectasis.…”
Section: Discussionsupporting
confidence: 89%
“…One patient in our study showed the crazy-paving pattern. This finding was previously described in immunocompetent patients (21,22). Another patient showed signs of chronic disease with irregular linear opacities and bronchiectasis.…”
Section: Discussionsupporting
confidence: 89%
“…However, there is a report that clinical fi ndings and imaging appearances are suggestive of small airway disease in H1N1 infection. 17 The characteristic peribronchial cuffi ng, air-trapping, and nodules in the present series may support this suggestion, and these CT fi ndings related to small airway disease might be a causative factor of severe dyspnea and, accordingly, be associated with a higher incidence of air-leak complication than with other types of infection in allergic or asthmatic patients.…”
Section: Discussionsupporting
confidence: 78%
“…Pulmonary emboli lobar, segmental and subsegmental pulmonary arteries, and unilateral or bilateral pleural effusion are defined in these patients. Alveolar hemorrhage is also observed, related to the viral infection [5, 6]. …”
Section: Discussionmentioning
confidence: 99%